TRANSFORMATION OF INFORMATION INTO KNOWLEDGE AT SOLVING THE MANAGEMENT TASKS - Tsechovoy, A. F.; A. V. Stepanov, A. V.; Zholtayeva, A. S. (Scientific Journal of Pedagogy and Economics, 2018)
The article considers the problems of people engaged in intellectual activity related to information overload. In the modern world, the amount of information with which managers, analysts and experts work is constantly growing. At that, the information required for daily work in the decision-making process is approximately constant in terms of volume. Due to which there is a problem of qualitative selection, filtering the flow of information with the transformation of its various forms: records, texts, documents into knowledge. The issue of transformation of information into knowledge is poorly understood in the scientific literature. The issues of how to arrange your thinking and organize your intellectual activity within the organization are of interest to people involved in management activities. It is important for them that the process of creating new knowledge be manageable and productive. To solve this problem, we offer the technology of the subject’s knowledge digitalization with Insight-DNA. In 2016, Insight-DNA technology with a wide range of applications was registered as a copyright object. In this article, we will disclose one aspect of the application of this technology – the creation of text products in the digitalization of knowledge. We believe that well-organized and structured knowledge is transmitted and perceived in text products. The emergence of digital knowledge technology in the market and creat